Women's Handball World Championship 2017 case study: European teams versus rest of the participating teams' efficiency - Leuciuc, F. V. (Acta Kinesiologica, 2018)
In this study we quantified data collected from the Women`s Handball World Championship 2017, held by Germany and in which 24 national teams (15 teams from Europe and 3 teams each from Asia, America and Africa) participated. The researchers analyze the game actions in handball in many ways in order to find solutions to improve performance. The aim of the study is to determine if there is any statistical significance between the European participating teams (15) and the rest of the World teams (9) in terms of efficiency during the competition. The data used in this article have been taken directly from the official statistics of the International Handball Federation. When we compare the efficiency of the European teams to the benchmark, for 6 out of 7 indicators the minimum requirements were achieved; for the rest of the participating teams at all indicators the values were below minimum recommendations. Regarding ANOVA univariate analysis for 7 out of 9 indicators there was obtained statistical significance (4 indicators for p < 0.05, 2 for < 0.01 and one for < 0.001) and this fact is confirmed by other studies. We can conclude that there is a statistical significance between the European teams and the rest of the participanting teams in term of efficiency at Women`s Handball World Championship 2017.These findings could be useful for individuals involved in handball activities and help them to find a proper manner to approach this kind of situations.